2022
DOI: 10.1029/2022jc019131
|View full text |Cite
|
Sign up to set email alerts
|

Global Mapping of Mesoscale Eddy Vertical Tilt

Abstract: Vertical motion induced by oceanic mesoscale eddies can strengthen ocean ventilation, and regulate vertical distribution of heat, dissolved CO2 and other tracers on a global scale. Eddy‐induced vertical motion is closely related to eddy vertical structure. Here, based on available satellite observations and Argo profiles, we find that mesoscale eddies in global oceans are prevalently vertical tilted. Anticyclonic eddies are frequently tilted westward and poleward from 300 dbar up to sea surface, while cyclonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…In the upper ocean (<300 m), the eddy centers generally tilt to the west with decreasing depth (blue lines). The composite eddies with westward tilted features in upper ocean have also been found in the North Pacific and the North Atlantic (e.g., Figure 6 in Roemmich & Gilson, 2001, Figure 3 in Amores et al., 2017, Figure 3 in Li et al., 2022). Interestingly, the composite eddies are also tilted eastward from deep ocean to subsurface (Figures 2a, 2b, 2d and 2e).…”
Section: Structure and Variability Of The Eddy Vertical Tiltmentioning
confidence: 60%
See 1 more Smart Citation
“…In the upper ocean (<300 m), the eddy centers generally tilt to the west with decreasing depth (blue lines). The composite eddies with westward tilted features in upper ocean have also been found in the North Pacific and the North Atlantic (e.g., Figure 6 in Roemmich & Gilson, 2001, Figure 3 in Amores et al., 2017, Figure 3 in Li et al., 2022). Interestingly, the composite eddies are also tilted eastward from deep ocean to subsurface (Figures 2a, 2b, 2d and 2e).…”
Section: Structure and Variability Of The Eddy Vertical Tiltmentioning
confidence: 60%
“…Vertical tilt of mesoscale eddies has been frequently observed in open oceans (e.g., Amores et al., 2017; Belkin et al., 2020; Bennett & White, 1986; Bernstein & White, 1981; Chen et al., 2012; Hu et al., 2011, 2022; Hua, 1988; Kurczyn et al., 2013; Li et al., 2022; Ni et al., 2021; Qiu & Chen, 2005; Roemmich & Gilson, 2001; Shu et al., 2019; Sun et al., 2022; Tang et al., 2020; The MODE Group, 1978; Zhang et al., 2016). These observed tilted eddies have various tilting directions (east‐west, north‐south) and tilting distance (TD; ∼6 km–∼150 km) from surface to deep ocean (Amores et al., 2017; Belkin et al., 2020; Bernstein & White, 1981; Kurczyn et al., 2013; Roemmich & Gilson, 2001; Sun et al., 2022; Tang et al., 2020; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Eddies are often tiled along the vertical direction due to their propagation [42]. However, the LV is a quasi-stationary ACE.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 8, a notable feature of the AE was that its vertical axis tilted toward the northeast from the sea surface to the deep layer with the tilting distance reaching approximately 220 km. The tilt of the vertical axis of mesoscale eddies has been frequently observed in the global oceans (e.g., Amores et al, 2017;Belkin et al, 2020;Kurczyn et al, 2013;Shu et al, 2019;Tang et al, 2020;Zhang et al, 2016), and several mechanisms are believed to contribute to the tilt of mesoscale eddies, such as topographic β-effect (Shu et al, 2019;Zhang et al, 2016), wind-induced Ekman advection (Stern, 1965;Tang et al, 2020), different translation speed and path of eddy with depth (H. Li et al, 2022;Liao et al, 2019), and so on. Based on hydrographic and mooring observations in this study, we explored the dynamics of the tilt of the AE axis, and found that the tilt of the AE could be attributed to strong stratification (Figure 9) and background shear flow in the upper layer (Figure 10).…”
Section: Vertical Structure Of the Aementioning
confidence: 99%
“…. In addition, H Li et al (2022). pointed out that the effect of stratification on the tilt of the eddy axis can be quantified by the nondi-), and the horizontal tilting distance of mesoscale eddies can be estimated from B u .…”
mentioning
confidence: 99%